Fabrication And Characterization Of Embedded Gold Nanoparticles In Metal Contacts For Silicon And Silicon Carbide-Based Devices - Gorji, Mohammad Saleh (2014)
Embedding metal nanoparticles (NPs) into metal contacts, at the interface with semiconductor, is an alternative method for modification of Schottky barrier height (SBH) in electrical contacts and offers a tremendous simplification and adaptation in processing steps. Schottky barrier diodes with aluminum (Al) contacts embedded with gold (Au) NPs on n- and p-type silicon (Si) and silicon carbide (4H-SiC) substrates were fabricated and their physical and electrical characteristics were investigated. Based on the studies on Si surface contact angle measurement and the negative zeta-potential values of seeded growth 20 nm Au NPs, an alternative approach was proposed to deposit Au NPs on linker-free n- and p-Si substrates using spin-coating technique. Density of NPs (determined by scanning electron microscope) on n-Si was substantially higher than p-Si which was due to the differences in surface properties of n- and p-Si. Current-voltage analysis of diodes revealed an increase in current density in both bias directions due to NPs local electric field enhancement effect and SBH lowering (0.1 1 eV for n- and 0.05 eV for p-Si). The electrical results were then correlated to the structural properties of Al/Si (determined by transmission electron microscope). Higher density of 5 and 10 nm Au NPs were deposited on SiC surface by using acidification technique with diluted HF. Al/4H-SiC diodes showed great improvement in SBH lowering (0.09 eV for n- and 0.24 eV for p-4H-SiC) and hence forward bias current density elevation while maintaining the rectification properties in reverse bias.